The Growth Response of Madeira Vine (Anredera cordifolia (Ten.) Steenis) on Different Levels of Shade and Applicationof Fertilizer and Biochar - Tapi Mutia Ariani Lubis; Yaya Hasanah; Nini Rahmawati (Talenta Publisher, 2018)
The intensity of the shade and fertilizer are the two aspects of the environment that important for the growth of madeira vine plants. The purpose of the research was to know the growth response of madeira vine on different levels shade and application of fertilizer and Biochar. The research was conducted in the research field of Faculty of Agriculture, Universitas Sumatera Utara, Medan about ± 32 m above the sea, on June to August 2017. This research used Split Plot Design with 2 factors, level of shade (0%; 25%; 50%; dan 75%) and application Fertilizer (without fertilizer; urea 1.6 g/plant; chicken manure 53.3 g/plant; biochar rice husk 294.4 g/plant). This results research showed that without shade (0%) increased the growth of plant length but the 75% shade increased of chlorophyll a, chlorophyll b, and total chlorophyll. Application of chicken manure was increasing plant length, shoot fresh weight but application biochar rice husk increased crop dry weight and leaf area. The interaction of different level shade and application of fertilizer was not significant affecting to the growth madeira vine plant in the end of observation.